Analisis kadar amilosa pada pati jagung manis (Zea Mays L. Var. Saccharata) secara spektrofotometri UV-Vis - Fadjria, Neri; Arfiandi, Arfiandi; Auliyah, Nabila Dhiyaul (Journal of Pharmaceutical and Sciences, 2024)
Sweet Corn Starch (Zea mays L. var. saccharata) is composed of two fractions: amylose and amylopectin. The determination of amylose content in Sweet Corn Starch is carried out using the spectrophotometric method. This method employs a 2% iodine solution as a reagent, which reacts with starch to generate a coloured solution that can be measured using a spectrophotometer. The amylose content is quantified through visible spectrophotometry, resulting in a regression equation of y ̂ = 0.006 + 25.2x, with a coefficient of determination (R2) = 0.998 and a correlation coefficient (r) = 0.9989. The amylose content in Sweet Corn Starch is determined to be 28.65%, whereas the amylopectin content is found to be 71.35%. Furthermore, the analysis provides additional parameters: Standard Deviation (SD) = ± 0.0044, Detection Limit (BD) = 0.0005 mg/ml, and Quantity Limit (BK) = 0.0018 mg/ml. These parameters offer valuable insights into the quality and properties of the sweet corn starch sample.